Lexikon der Mensch-Tier-Beziehungen - Petrus, Klaus; Ferrari, Arianna (transcript, 2015)
Our relationship with »other« animals is not only becoming socially ever more significant, it has also been rediscovered as a topic for the humanities and sciences.This volume is the first encyclopedia to devote itself comprehensively to the relationship between humans and animals. In contrast to traditional introductions into animal ethics, the large-scale work does not limit itself to issues of moral philosophy but also explores the human-animal relationship from a historical, sociological, ethological and cultural perspective.